WISC-IV performance of South African grade 7 English and Xhosa speaking children with advantaged versus disadvantaged education - Van Tonder, Phia (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
Research reveals that the level as well as the quality of education plays a role in the determination of an individual's intellectual capacity. Substantial differences in quality of education for black and white individuals were experienced in South Africa due to Apartheid. Compared to the traditionally white Private and Model C schools, Township/ DET schools had limited resources, as well as a separate syllabus and examination system, a situation that has not improved substantially since democratisation in 1994. Research on black South African adults with the WAIS-III has confirmed significant influences on IQ in association with exposure to either such advantaged (Private/Model C) schooling, or disadvantaged (Township/DET) schooling. However to date there has been no published research on the use of the Wechsler intelligence tests on a black South African child population similarly stratified for quality of education. Therefore, for the purposes of this study, the latest Wechsler Intelligence Scale for Children (WISC-IV) was administered to a sample of 36 Grade 7 learners between the ages of 12-13 (mean 13.01 years), stratified for quality of education to form three comparative groups. Data analyses revealed significant differences on the WISC-IV Factor Indices and Full Scale IQ with the English speaking Private/Model C school group performing the best, followed by the Xhosa speaking Private/ Model C school group, and the Xhosa speaking Township/ DET school group performing the worst. This continuum of lowering is understood to occur abreast of a continuum of decreased exposure to relatively advantaged education. These normative indications are considered to have vital implications for the use of the WISC-IV in the South African cross-cultural situation where vastly differential educational opportunities continue to exist.
Keywords: Wechsler Intelligence Scale for Children; Intelligence tests -- South Africa; Educational tests and measurements -- South Africa; Psychological tests -- Cross-cultural studies; Educational psychology -- South Africa; Language and languages -- Ability testing; Educational evaluation -- South Africa; Education, Elementary -- South Africa